Reduced 15N Losses by Winter and Spring Night-Warming Are Related to Root Distribution of Winter Wheat - Hu, Chenxi; Yu, Jinghong; Sun, Shuzhen; Yan, Yanyan; Guo, Hua; Tian, Zhongwei; Jiang, Dong; Cao, Weixing; Dai, Tingbo (Frontiers in Plant Science, 2019)
To develop efficient N management strategies for high wheat NUE and minimizing the environmental impact of N losses under asymmetric warming, 15N micro–plot experiments were conducted to investigate the effects of night–warming during winter (warming by 1.47–1.56 °C from tillering to jointing), spring (warming by 1.68–1.82 °C from jointing to booting), and winter + spring (warming by 1.53–1.64 °C from tillering to booting) on root growth and distribution of winter wheat, the fates of 15N–labelled fertilizer, and their relationships in 2015–2017. The results showed that night–warming increased the recovery of basal 15N and top–dressed 15N, while reduced the residual and loss of basal 15N and top–dressed 15N. The losses decreases of top–dressed 15N were higher than those of basal 15N, indicating that night–warming reduced losses of fertilizer 15N mainly by reducing losses of top–dressed 15N. Moreover, pre–anthesis root dry matter accumulation rate in 0–60 cm soil layer were promoted, resulted in improved root biomass and root/shoot ratio, which favored increasing recovery of fertilizer 15N and reducing losses of fertilizer 15N. Furthermore, residual fertilizer 15N content in 0–100 cm soil layer was reduced, which was associated with improved root weight density in 0–60 cm soil layer, resulted in reduced leaching losses of fertilizer 15N. The path analysis showed that root dry matter distribution in 0–20 cm soil layer was the most important in contributing to reducing losses of total fertilizer 15N compared with other soil layers. Two years data showed that winter and spring night–warming gave better root growth and distribution in 0–20 cm soil layer, resulted in reduced the losses of fertilizer 15N and improved the recovery of fertilizer 15N, while maximizing grain yield of winter wheat, and winter + spring night–warming resulted in higher advantages than winter night–warming and spring night–warming.